FEATURE DETECTION FOR REALISTIC IMAGES BASED ON B-SPLINES OF 3rd ORDER RELATED TO INTERPOLAR ON AVERAGE - Pristavka, Philip; Tyvodar, Oksana; Martyuk, Bogdan (Proceedings of National Aviation University (archive), 2017)
Purpose: One approach where recognition of objects in a digital image is based on a search for special points of the function of two variables model intensity lighting. As a model proposed to use a two-dimensional polynomial spline-based B-splines of order. For linear operators that determine the characteristics of a digital image is necessary to conduct appropriate studies partial derivatives of first and second order spline said. Methods: Active obtaining explicit views of partial derivatives and study of their standards and quality of approximation, further defining particular cases suitable for implementation in the software. Results: The paper proposes a calculation of differentials and their partial cases for two-dimensional polynomial spline based on B-splines of third order. Based on these, analogs of known operators that determine the local characteristics of digital images were proposed. Discussion: Further research may be to obtain similar operators based on combinations of two-dimensional B-spline above the second order analysis capabilities and their application to problems of digital imaging and video